Qualitative insights into promotion of pharmaceutical products in Bangladesh: how ethical are the practices? - Mohiuddin, Mahrukh; Rashid, Sabina Faiz; Shuvro, Mofijul Islam; Nahar, Nahitun; Ahmed, Syed Masud (BMC Medical Ethics, 2016)
Includes bibliographical references (page 9).